Acinar cystic transformation of the pancreas—a rare case in a young patient. Issue 2 (27th February 2023) - Steinkraus, Kira Carlotta; Mühlberger, Michael; Schmidt, Stefan Andreas; Kornmann, Marko
Abstract: Acinar cystic transformation (ACT) is a very rare transformation of the pancreas and has been described in less than 100 cases since its first report in 2002. The aim of this case report is to get a better understanding of this pancreatic transformation, which to date appears to be non-malignant. However, radical surgery was performed in most cases due to misinterpreting the initial diagnosis. ACT may be misdiagnosed for intraductal papillary mucinous neoplasms and is currently not included as a potential differential diagnosis for cystic lesions of the pancreas. ACT belongs to the benign cystic alterations of the pancreas. Despite its rarity, it should be considered as a potential differential diagnosis with regard to cystic lesions in the pancreas, especially in order to avoid unnecessary surgery.